Model Matematis Hubungan antara Kadar Air Akhir Bahan dengan Variabel Proses Pengeringan pada Pneumatic Conveying Recirculated Dryer - Abadi Jading; Nursigit Bintoro; Lilik Sutiarso; Joko Nugroho Wahyu Karyadi (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2018)
Flour drying could be conducted by using pneumatic conveying dryer (PCD) or flash dryer, but generally it is required a high vertical pipe. The high of vertical pipe may be replaced with a recirculation process to produce a required final moisture content of the material. This study had designed pneumatic conveying recirculated dryer (PCRD) to dryi of wet sago starch. Later, the design was used to determine a mathematical model of the relationship between the variables of drying process with final moisture content of the material. The purpose of this study was to develop a mathematical model of the relationship between the final moisture content of wet sago starch with variables drying process and recirculation continuously in the pneumatic conveying recirculated dryer (PCRD) using dimensional analysis. Buckingham Phi Theorem methods of dimensional analysis was used to find the relationship variables that affect the final moisture content of wet sago starch on the PCRD machine. The mathematical model generated in this study is The coefficient of determination (R2) of the mathematical model was 0.948, or 94.8 %, indicated that the model was valid to predict the final moisture content of wet sago starch in designing PCRD machines. While the sensitivity of the test results showed that the dimensionless product of the most influential are , , and . The model was applicable for drying wet sago starch or other starch material which is similat to the physical properties of wet sago starch. ABSTRAKPengeringan bahan-bahan tepung dapat dilakukan dengan pneumatic conveying dryer (PCD) atau flash dryer, namun umumnya memerlukan pipa vertikal yang cukup tinggi. Pipa vertikal yang tinggi dapat diganti dengan proses resirkulasi untuk menghasilkan kadar air akhir bahan yang disyaratkan. Pada penelitian ini telah dirancang pneumatic conveying recirculated dryer (PCRD) untuk mengeringkan pati sagu basah, serta dicari model hubungan matematis antara variabel-variabel proses pengeringan dengan kadar air akhir. Tujuan penelitian ini adalah mengembangkan model matematis hubungan antara kadar air akhir pati sagu basah dengan variabel-variabel proses pengeringan resirkulasi secara kontinyu pada pneumatic conveying recirculated dryer (PCRD) menggunakan analisis dimensi. Metode Buckingham Phi Theorem dalam analisis dimensi digunakan untuk mencari hubungan variabel-variabel yang berpengaruh terhadap kadar air akhir pati sagu basah pada mesin PCRD. Model matematis yang dihasilkan pada penelitian ini adalah Nilai koefisien determinasi (R2) dari model matematis tersebut adalah 0,948 atau 94,8 %, menunjukkan bahwa model tersebut valid digunakan untuk memprediksi kadar air akhir pati sagu basah dalam merancang mesin PCRD. Sedangkan hasil uji sensitivitas menunjukkan bahwa dimensionless product yang paling berpengaruh adalah , , dan . Model tersebut berlaku untuk pengeringan pati sagu basah atau bahan-bahan tepung lainnya yang sifat fisiknya identik dengan pati sagu basah.